2020
DOI: 10.1002/em.22412
|View full text |Cite
|
Sign up to set email alerts
|

Heritable hazards of smoking: Applying the “clean sheet” framework to further science and policy

Abstract: All the cells in our bodies are derived from the germ cells of our parents, just as our own germ cells become the bodies of our children. The integrity of the genetic information inherited from these germ cells is of paramount importance in establishing the health of each generation and perpetuating our species into the future. There is a large and growing body of evidence strongly suggesting the existence of substances that may threaten this integrity by acting as human germ cell mutagens. However, there gene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 53 publications
0
5
0
Order By: Relevance
“…The same study reinforced by Azmiyardi (2020) also found there was an effect of smoking A study from Bline et al (2020) shows that tobacco smoke exposure has inheritable effects on germ cells, with negative health implications for the resulting offspring. Given the historical prevalence of tobacco smoking, it is also a substance with a legacy of exposure that is carried among us today and will continue to be passed along to the next generations.…”
Section: Discussionmentioning
confidence: 83%
“…The same study reinforced by Azmiyardi (2020) also found there was an effect of smoking A study from Bline et al (2020) shows that tobacco smoke exposure has inheritable effects on germ cells, with negative health implications for the resulting offspring. Given the historical prevalence of tobacco smoking, it is also a substance with a legacy of exposure that is carried among us today and will continue to be passed along to the next generations.…”
Section: Discussionmentioning
confidence: 83%
“…Furthermore, SCSA has been suggested to be a suitable method to study DNA fragmentation due to chemical exposure 35 that is mutagenic to male germ cells 36 . This suggestion is supported by studies reporting that mutagenic exposure increases sperm DNA fragmentation according to both SCSA and the TUNEL assay, 37 similar to the increase seen by SCSA after tobacco smoke exposure, 38 which as mentioned has also been suggested to be mutagenic to human germ cells, 39–41 and reported to give rise to mutations in both sperm 42 and spermatogonial stem cells 43 of mice. Accordingly, the aim of this study was to investigate whether urinary levels of 1‐OHP, 2‐OHPH and cotinine, as biomarkers of exposure to PAH and nicotine, were associated with sperm DNA fragmentation in Swedish men from the general population.…”
Section: Introductionmentioning
confidence: 80%
“…10 However, aside from ageing, the existence of human germ cell mutagens has yet to be convincingly demonstrated. 11 Nonetheless, recent studies applying whole genome sequencing to human families provide intriguing support that certain pharmaceuticals and lifestyle factors cause DNMs in offspring via paternal germ cells. 10,12,13…”
Section: Introductionmentioning
confidence: 99%